Evolutionary game analysis of Arctic shipping black carbon emission reduction strategies based on government regulation and port fee differential policies - Xinli Qi; Zhenfu Li; Yiran Zhang; Qiqi Zhang; Chunrui Song (Humanities & Social Sciences Communications)
Abstract The issue of black carbon (BC) emissions from Arctic shipping has garnered significant attention from the international community. Promoting action among key stakeholders is particularly critical at this juncture. This study constructed a BC emissions governance model for Arctic shipping based on government regulation and differential port fee policies, and established an evolutionary game model of Arctic coastal governments, ports and shipping companies, analyzing the impact of evolutionary steady state and various parameter variables on the choice of stakeholder behavioral strategies. The results show that $${E}_{8}(1,1,1)$$ E 8 ( 1,1,1 ) is the optimal steady-state case for the system, which means active government regulation along the Arctic, implementation of port fee differential policies by port, and active emission reductions by shipping companies. During the game process, each participant’s strategy is influenced by the initial choices made by other participants. Among them, the coastal government’s first supervision is the key factor in promoting the emission reduction behavior of the shipping industry. At the same time, appropriate coastal government reward and punishment mechanisms and differential port fee policies play a decisive role in emission control. If the policy intensity is too low, shipping companies may lack action for a long time. Excessive policy intensity may affect the long-term sustainability of the policy. In addition, lower emission reduction technology costs help to enhance the willingness of shipping companies to reduce emissions. On the contrary, high technology costs will weaken their enthusiasm and may cause the government to turn to passive regulation due to regulatory costs and delayed market response. Overall, to achieve the desired stabilization strategy for BC emission reductions in Arctic shipping, collective action is essential.